The Effect of Employee Engagement and Work-life Balance to Employee Performance with Job Satisfaction as a Mediation Variable in Lavalette Hospital Malang - Panji Arik Indraswara; Umu Khouroh; Andini Risfandini (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
Hospitals are a health service industry which are now increasingly required to continue to adapt to developments and provide the best service for the community. Now, the current very tight competition requires hospitals to continue to improve the quality of their services. Lavalette Hospital is developing and continues to strive to provide the best service to the community by improving the performance of human resources. There are many factors that can influence employee performance, including employee engagement, work-life balance and job satisfaction as factors that can strengthen this influence. For this reason, this research aims to analyze the influence of employee engagement, work-life balance on employee performance with job satisfaction as a mediating variable at Lavalette Hospital Malang. The sample in this study was 167 respondents consisting of PWT and PWTT employees using a simple random sampling. The data collection technique uses a Google form which is distributed to respondents. Data analysis was carried out using SEM PLS analysis using SmartPLS 4.0. The research results showed that:1.Employee engagement has a significant effect on job satisfaction, 2.Work-life balance has a significant effect on job satisfaction,3.Employee engagement has a significant effect on employee performance,4.Work-life balance has a significant effect on employee performance,5.Job satisfaction has a significant effect on employee performance,6.Employee engagement has a significant effect on performance employees with job satisfaction as a mediating variable,7.Work-life balance does not have a significant effect on employee performance with job satisfaction as a mediating variable.